Belki v peredelke - Bright, Rachel (Poli͡andrii͡a Print, 2017)
Two greedy squirrels learn to share in the third hilarious rhyming adventure from the bestselling creators of The lion inside. Greedy squirrels Cyril and Bruce both have their sights on a very special prize: THE VERY LAST NUT OF THE SEASON! As the nut bounces crazily though the forest, the squirrels race after it, between the trees, over boulders, down the river and - ARGH! - right to the edge of a waterfall! Working together might be the only way to save themselves now ... A laugh-out-loud tale about friendship and sharing.